Hepatitis B virus surface antigen binds to apolipoprotein H. - Mehdi, H (1994)
We have previously demonstrated that a plasma membrane-enriched fraction isolated from human liver is capable of binding recombinant hepatitis B surface antigen (rHBsAg) (P. Pontisso, M. A. Petit, M. Bankowski, and M. E. Peeples, J. Virol. 63:1981-1988, 1989). In this study we have separated the plasma membrane proteins by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and used a ligand-blotting technique to identify a 46-kDa rHBsAg-binding protein. This protein could be removed from the membranes with a weakly acidic buffer, implying that it is peripherally bound. Examination of human serum revealed that the 46-kDa binding protein is a serum protein. Isolation of plasma lipoproteins revealed that the binding protein is in part associated with chylomicrons and high-density lipoproteins, both of which are targeted to the hepatocyte during the normal course of lipid metabolism. The binding protein was identified as apolipoprotein H (apo H), also known as beta 2-glycoprotein I, on the basis of copurification of the rHBsAg-binding activity with the apo H protein and the ability of cDNA-expressed apo H to bind rHBsAg. Serum-derived HBsAg also binds to apo H, indicating that binding is not unique to rHBsAg. Binding is saturable, requires only the small S protein of rHBsAg, and is inhibited by excess rHBsAg, antibodies to HBsAg, and antibodies to apo H. The binding activity of apo H is destroyed upon reduction, indicating that 1 or more of its 22 disulfide bonds are required for interaction with rHBsAg. The possibility that an interaction between hepatitis B virus particles and lipoprotein particles may facilitate entry of the virus into hepatocytes is discussed.